2023
DOI: 10.3390/su151511811
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Differences and Drivers of Tourism Ecological Security in China’s Border Areas

Abstract: Tourism activities generally have a ∩-type lock on the level of tourism ecological security in an area, but when applied to the border areas of China, there are certain specificities in the spatial evolution of tourism ecological security (TES) compared to traditional findings. This paper measures tourism ecological security in China’s border areas from 2009 to 2020 by using the DPSIR model with the SBM-DEA and analyzes the spatial differences, evolutionary characteristics, and driving factors of tourism ecolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…The aim is for the two to produce benign promotion and protect the ecological environment while developing rural tourism. The coupling coordination of this study is shown in Table 1 (Wang et al, 2023).…”
Section: Research Methods and Protocolsmentioning
confidence: 99%
“…The aim is for the two to produce benign promotion and protect the ecological environment while developing rural tourism. The coupling coordination of this study is shown in Table 1 (Wang et al, 2023).…”
Section: Research Methods and Protocolsmentioning
confidence: 99%
“…However, the research on China's border tourism has mainly focused on national-level border tourism destinations or specific regional studies on border tourism spatial structures, tourist flows, development strategies, and regional systems in Northeast China, Southwest China, Xinjiang, and other regions. There has been no specific research on the Qinghai-Tibet Plateau border region [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…With the depth of the study, the focus of scholars shifted to a higher level of analysis concerning influencing factors. Scholars generally believe that population density, economic level, government capacity, and scientific and technological investment are the main factors affecting tourism-related ecological security [29,30], usually with the help of the gray correlation projection method [31], barrier degree model [32], geographic detector [33], structural equation modeling [34], etc., and the large quantity of practical evidence that has been collected. The research objects involve watersheds [35,36], provinces [36], cities [37][38][39], parks [40,41], scenic areas [42,43], islands [44,45], and mountains [46,47].…”
Section: Introductionmentioning
confidence: 99%